Complications in orofacial harmonization procedures: a systematic review - Nathalia Lopes Manganaro; Julia Gabriela Dietrichkeit Pereira; Ricardo Henrique Alves da Silva (Revista Brasileira de Cirurgia Plástica, 2022)
Currently, facial aesthetic changes and dissatisfaction with self-image are influences that motivate the search for quick, non-surgical and less invasive cosmetic procedures. For this reason, the demand for patients looking for orofacial aesthetic procedures is increasing. The objective of this study was List the complications resulting from orofacial harmonization procedures through a systematic literature review, identifying which types of complications and areas are most affected. The following databases were searched: Medline (PubMed), SciELO, Scopus, Cochrane, Lilacs and Web of Science, from March to September 2020, selecting the studies that presented the following inclusion criteria: original studies in humans, about complications after orofacial harmonization procedures. Thirty-three studies from the literature were selected that presented reports of complications in patients after the orofacial harmonization procedure in the forehead, nose, eyes, periocular region and lips. Even the execution of less invasive facial cosmetic procedures can cause possible immediate or late complications after the procedure, especially in the periocular region and eyes. It is important to make professionals aware of this possibility beforehand.